Towards digital counselling in primary care management of symptomatic knee osteoarthritis: a qualitative descriptive study in Finnish primary care - Miia Jansson; Maria Kääriäinen; Gillian Vesty; Minna Pikkarainen (Finnish Journal of eHealth and eWelfare, 2023)
Digital counselling may improve patients’ health outcomes, when eHealth solutions are accessible and tailored to the patients’ needs, which is especially important for people with chronic and long-term conditions such as knee osteoarthritis. This study aims to identify patients’ eHealth needs to improve the quality of digital counselling in a primary care management of symptomatic knee osteoarthritis. A qualitative study was used to collect patients’ eHealth needs through semi-structured interviews in a single outpatient clinic in Finland between August 2020 and November 2020. The data was analyzed using both deductive and inductive content analysis approaches. The study was reported in accordance with the Consolidated Criteria for Reporting Qualitative research checklist to improve the transparency of the study.